Validity and Acceptability of Wearable Devices for Monitoring Step-Count and Activity Minutes Among People With Multiple Sclerosis - Lavelle, Grace; Norris, Meriel; Flemming, Julie; Harper, Jamie; Bradley, Joan; Johnston, Helen; Fortune, Jennifer; Stennett, Andrea; Kilbride, Cherry; Ryan, Jennifer M. (Frontiers in Rehabilitation Sciences, 2022)
Multiple wearable devices that purport to measure physical activity are widely available to consumers. While they may support increases in physical activity among people with multiple sclerosis (MS) by providing feedback on their performance, there is little information about the validity and acceptability of these devices. Providing devices that are perceived as inaccurate and difficult to use may have negative consequences for people with MS, rather than supporting participation in physical activity. The aim of this study was to assess the validity and acceptability of commercially available devices for monitoring step-count and activity time among people with MS. Nineteen ambulatory adults with MS (mean [standard deviation] age 52.1 [11.9] years) participated in the study. Step-count was assessed using five commercially available devices (Fitbit Alta, Fitbit Zip, Garmin Vivofit 4, Yamax Digi Walker SW200, Letscom monitor) and an activPAL3µ while completing nine everyday activities. Step-count was also manually counted. Time in light activity, moderate-to-vigorous activity and total activity was measured during activities using an Actigraph GT3X accelerometer. Fifteen participants wore five commercially available devices for three consecutive days each, and participated in a semi-structured interview regarding their perception of the acceptability of the monitor. Mean percentage error for step-count ranged from 12.1% for the Yamax SW200 to -112.3% for the Letscom. Mean step-count as manually determined differed to mean step-count measured by the Fitbit Alta (p=0.002), Garmin Vivofit (p<0.001), Letscom (p<0.001) and activPAL3µ (p<0.001). However, 95% limits of agreement were smallest for the activPAL3µ and largest for the Fitbit Alta. Median percentage error for activity minutes was 52.9% for the Letscom and 100% for the Garmin Vivofit and Fitbit Alta compared to minutes in total activity. Three inductive themes were generated from participant accounts: Interaction with device; The way the device looks and feels; Functionality. In conclusion, commercially available devices demonstrated poor criterion validity when measuring step-count and activity time in people with MS. This negatively affected the acceptability of devices, with perceived inaccuracies causing distrust and frustration. Additional considerations when designing devices for people with MS include an appropriately sized and lit display and ease of attaching and charging devices.